FRI0170 Incidence and Risk Factors for Osteoporotic Vertebral Fracture in Brazilian Community-Dwelling Elderly: A Population-Based Prospective Cohort Analysis from the SÃO Paulo Ageing & Health (SPAH) Study. (10th June 2014) - Domiciano, D.S.; Machado, L.G.; Lopes, J.; Figueiredo, C.; Menezes, P.; Caparbo, V.; Takayama, L.; Pereira, R.M.R.
Abstract : Background: In contrast to hip fracture, prospective data about the incidence of osteoporotic vertebral fracture are scarce and all studies were originated from developed countries. No consistent data on incidence of vertebral fractures have been reported in low and middle income countries where the population ageing has been faster. Objectives: To describe the incidence and predictors of radiographic vertebral fracture in a population-based cohort of Brazilian older adults. Methods: 707 community-dwelling older subjects aged over 65 years (449 women, mean age 72.9±4.8 years, and 258 men, mean age 72.3±4.7 years), were studied. Spinal radiographs were obtained at baseline and after a mean follow-up of 4.3 years. Using the semiquantitative method, new vertebral fracture was considered as a distinct alteration in morphology of vertebral body resulting in higher grade (grade 1–3) when the radiograph was compared to the same vertebrae on the baseline. Clinical data obtained by specific questionnaire, bone mineral density measurement (BMD) by DXA and laboratorial bone exams were also performed at baseline. Multivariate Poisson regression models were used to identify independent predictors of vertebral fracture. Results: After a mean 4.3±0.8 years of follow-up, the age standardized incidence of vertebral fracture was 40.3/1000 person years (pyr) in women and 30.6/1000 pyr in men. The incidence increased with age, mainly in women. In women, the final Poisson regression revealed three possible models of independent predictors of fracture: 1. age (RR 2.46, 95% CI 1.66-3.65, p<0.001, per each 10-year increase), prior osteoporotic fracture (RR 1.65, 95% CI 1.00-2.71, p=0.049) and BMD at lumbar spine (RR 1.21, 95% CI 1.03-1.41, p=0.017, per each 1 SD reduction at BMD); 2. age (RR 2.25, 95% CI 1.52-3.34, p<0.001) and femoral neck BMD (RR 1.42, 95% CI 1.11-1.81, p=0.006); and 3. age (RR 2.11, 95% CI 1.41-3.15, p<0.001) and BMD at total hip (RR 1.56, 95% CI 1.21-2.01, p=0.001). Although the risk ratios were of borderline significance, highest quartile of serum CTX (>0.440ng/mL) (RR 1.96, 95% CI 0.98-3.91, p=0.057) and prior osteoporotic fracture (RR 2.10, 95% CI 1.00-4.39, p=0.050) were independent predictors of new fracture in men. A new multivariate analysis excluding mild (grade 1) vertebral deformities retained total hip BMD (RR 1.46, 95% CI 1.02-2.09, p=0.038) and calcium intake from dairy product consumption (RR 1.19, 95% CI 1.02-1.39, p=0.028, per each decrease of 100mg/day) as independent risk factors for moderate/severe fracture in women, whereas BMD at total hip (RR 2.01, 95% CI 1.04-3.88, p=0.038) was the strongest predictor of moderate/severe fracture in men. Conclusions: This is the first population-based study to ascertain the incidence of vertebral fracture in elderly in Latin America. The data confirm the high frequency of the disorder in Brazilian older adults and the rise in incidence with age. Age, BMD, prior fracture and bone turnover were predictors of short-term incidence of vertebral fracture. These results reinforce the importance of focusing efforts to prevent vertebral fractures. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1611